ACE I/D Polymorphism in Brazilian Women with Endometriosis - Gabriela Rister Figueiredo Irie; Marly Aparecida Spadotto Balarin; Mariangela Torreglosa Ruiz-Cintra; Mariana Kefalas Oliveira Gomes; Marco Fabio Prata Lima; Alessandra Bernadete Trovó de Marqui (São Paulo State University (UNESP), 2016)
Endometriosis is a chronic gynecological disease that displays some features similar to malignancy, such as local invasion, aggressive spread to distant organs and angiogenesis. Polymorphisms of the ACE gene have been linked with some vascular disease. To determine the frequency of the ACE I/D polymorphism in Brazilian patients with endometriosis compared to controls. This case-control study included a total of 134 women (49 endometriosis patients and 85 controls) who had undergone a laparoscopy or laparotomy. Molecular analysis was performed by polymerase chain reaction (PCR). For the statistical analysis, the chi-square and multiple logistic regression tests were used. The I/D ACE genotype frequencies in cases and controls were, respectively: II 16.3% and 16.5%; ID 24.5% and 20%; DD 59.2% and 63.5%. There was no statistically significant difference between cases and controls, either in the genotype frequencies (χ2 = 0.385; p = 0.825) or in the allele frequencies (χ2 = 0.098; p = 0.75) of the ACE I/D polymorphism. However, the genotype distribution was not consistent with the Hardy-Weinberg equilibrium, either in patients (χ2 = 7.84; p = 0.005) or in controls (χ2 = 20.09; p <0.0001). Multiple logistic regression analysis has not shown any differences amongst groups for the polymorphism studied [(OR 1.51; CI 95% 0.52- 4.41); p=0.4523]. Despite of the small sample size, the present study suggests that I/D ACE polymorphism is not related with endometriosis in brazilian patients.